A physical and chemical double enhancement strategy for 3D printing of cellulose reinforced nanocomposite. Issue 39 (7th March 2020) - Wang, Bo; Ding, Guojiao; Chen, Ken; Jia, Shuai; Wei, Jie; Wang, Yongzhi; He, Rujie; Shao, Ziqiang
Abstract: Nanocellulose as reinforcing filler added into resin matrix has been widely used in many studies, but it remains challenging when some rigorous applications are taken into consideration. In this study, a novel nanocomposite with high performance was successfully developed for stereolithography (SLA) through physical (cellulose nanocrystal [CNC] physical enhancement) and chemical (esterification reaction) double enhancement effects during post‐curing process. Compound additive (CA), composed of CNCs, butanetetracarboxylic acid, and sodium hypophosphite, were added into methacrylic acid resin to form a novel nanocomposite for SLA and post‐curing. Mechanical properties of samples added with CA were better than those added with CNC only. When the content of CNC in the CA was 0.5 wt%, the sample possessed optimal mechanical properties and improved thermal stability after post‐curing. Meanwhile, dynamic mechanical analysis showed that samples added with CA improved storage modulus and meaningfully increased toughness when used at near room temperature. Abstract :